Customer-driven menu analysis (CDMA): Capturing customer voice in menu management. (October 2020) - Nemeschansky, Ben; von der Heidt, Tania; Kim, Peter Beomcheol
Highlights: Many menu analysis approaches focus internally on the organisation and thus ignore value from the customers' perspective. The CDMA model embeds the customer perspective at every stage of menu analysis. The CDMA model demonstrates that the key element is externally-defined value (as defined by the customer). The CDMA model is a cyclical process that ensures that the customer's voice is always heard and never lost. The CDMA model can be applied to several different menu analysis methodologies. Abstract: This study develops a new, holistic, customer-driven menu analysis (CDMA) model that incorporates a version of restaurant profitability analysis based on experience accounting and value-based cost management. The CDMA model comprises four stages: the customer's voice; cost allocation; menu analysis; and profitability analysis. A constructive research approach was used to develop, elaborate and test the new CDMA model in the context of a large restaurant in Auckland, New Zealand. The model can be used by restaurateurs to view their cost structure in a fully customer-driven and nuanced way to improve operational and financial decision-making for enhanced restaurant performance.